Guide to the trematodes (Platyhelminthes) that infect the California horn snail (Cerithideopsis californica: Potamididae: Gastropoda) as first intermediate host - Hechinger, Ryan F (Zootaxa, 2019)
The California horn snail, Cerithideopsis californica, lives in estuarine habitats from California (USA) in North America to Piura (Peru) in South America. Throughout this range, the snail serves as first intermediate host for a diverse guild of digenean trematodes. These parasites are used in teaching laboratories, and have been subject to a large amount of taxonomic, biological, evolutionary, and ecological research. Despite the abundance of research on these trematodes, we lack a satisfactory guide to these parasites. This manuscript treats the 19 trematode species that we are currently able to distinguish morphologically. I provide taxonomic affinities, information on second intermediate host use, an identification key focused on cercaria traits, information and a key for regressed infections lacking cercariae, information on early infections, and species accounts. The species accounts present photographs, additional diagnostic information, taxonomic notes, information concerning cryptic species, and connections to relevant literature. The primary aim of this manuscript is to facilitate research on this trematode guild by serving as an identification tool, and by providing background information, including highlighting gaps in our knowledge.